The negative impact of social microenvironment on the formation of the criminal personality - Nikishkin A. V., Vetrova E. V., Ekimova A. I. (Topical issues of law, economic and management, 2019)
the authors consider the comprehensive influence of the social environment on the offender. The negative impact of family, labor collective and informal relations on the development and maturation of the individual as a member of society is revealed.
Keywords: социальная среда; семейное воспитание; professional orientation; профессиональная направленность; криминогенная направленность; микроокружение; индивидуальный опыт; преступные группировки; неблагоприятное влияние; social environment; family education; criminogenic orientation; microenvironment; individual experience; criminal groups; adverse influence